ANALISIS MANAJEMEN BISNIS SYARIAH BADAN USAHA MILIK DESA CIBITUNG WETAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Zulkarnaen, Muhammad Ryandika; Trihantana, Rully; Melinasari, Susi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
Village-Owned Enterprises (BUMDes) are business entities whose capital is wholly or largely owned by the Village through direct participation originating from Village assets which are separated to manage assets, services and other businesses for the greatest welfare of the Village community. In an effort to improve the standard of living of the community, the Cibitung Wetan Village Government, Pamijahan District, Bogor Regency, West Java Province, established the Kahuripan Village Owned Enterprise (BUMDes Kahuripan). In this research the author discusses the analysis of the sharia business management of BUMDes Kahuripan in empowering the community of Cibitung Wetan Village, through business and economic development. This descriptive qualitative research, with sharia business management analysis, resulted that efforts to implement the Kahuripan BUMDes business to improve the economic life of the community were relatively good. This can be seen from the running of the business owned by BUMDes Kahuripan. BUMDes Kahuripan also plays a role in increasing community enthusiasm to be creative and innovative in entrepreneurship.